Silicosis and lung cancer among workers in North Carolina dusty trades - Amandus, H. E.; Shy, C.; Castellan, R. M.; Blair, Aaron; Heineman, E. F. (Scandinavian Journal of Work, Environment & Health, 1995)
In 1940–1983, 760 cases of silicosis were identified among male North Carolina (NC) workers in dusty trades. Vital status was ascertained through 1983 for 714 silicotics, and death certificates were obtained for 546 of the 550 decedents. The standardized mortality ratio (SMR) for lung cancer based on United States rates was 2.6 [95% confidence interval (95% CI) 1.8–3.6] for whites, 2.3 (95% CI 1.5–3.4) for whites unexposed to other known occupational carcinogens, and 2.4 (95% CI 1.5–3.6) for whites with no other exposure and diagnosed with silicosis while still employed in dusty trades. In addition, the age- and smoking-adjusted rate for silicotics was 3.9) times higher (95% CI 2.4–6.4 than that of nonsilicotic metal miners. This analysis effectively controlled for confounding by age, cigarette smoking, exposure to other occupational carcinogens, and detection bias. The results congrue with the hypothesis of an association between silicosis and lung cancer.
Keywords: dusty trades; lung cancer; silicosis